Associations of Dietary Vitamin C and E Intake With Depression. A Meta-Analysis of Observational Studies - Ding, Jun; Zhang, Yi (Frontiers in Nutrition, 2022)
Objective The associations of dietary vitamin C and E intake with depression remains conflicting. This meta-analysis of observational study was therefore employed to clarify the issue further. Methods An extensive literature review (PubMed, Web of Science and Embase) was performed in January 2022 to identify the observational studies on the associations of dietary vitamin C and E intake with depression. The pooled relative risk (RR) of depression for the highest versus lowest dietary vitamin C and E intake category, and the weighted mean difference (WMD) of dietary vitamin C and E intake for depression versus control subjects, were calculated. Results A total of 25 observational studies (91966 participants) were included in this meta-analysis. The overall multi-variable adjusted RR demonstrated that dietary vitamin C intake was inversely associated with depression (RR = 0.72, 95% CI: 0.57 to 0.91; P = 0.005). In addition, the combined WMD showed that the dietary vitamin C intake in depression was lower than that in control subjects (WMD = −11.58, 95% CI: −14.88 to −8.29; P < 0.001). Similarly, the overall multi-variable adjusted RR demonstrated that dietary vitamin E intake was negatively associated with depression (RR = 0.84, 95% CI: 0.72 to 0.98; P = 0.02). Moreover, the combined WMD showed that the dietary vitamin E intake in depression was also lower than that in control subjects (WMD = −0.71, 95% CI: −1.07 to −0.34; P < 0.001). Conclusion The results of this meta-analysis suggest that both dietary vitamin C and E intake is inversely associated with depression. However, due to the limited evidence, more well-designed prospective cohort studies are still needed.